2007
DOI: 10.1086/523591
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of Active Tuberculous Serositis by Antigen-Specific Interferon-  Response of Cavity Fluid Cells

Abstract: The cavity fluid IFN-gamma assay could be a method for accurately and promptly diagnosing active tuberculous serositis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
45
1
2

Year Published

2009
2009
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(49 citation statements)
references
References 26 publications
1
45
1
2
Order By: Relevance
“…Two recent preliminary studies from low-burden countries (Europe and Japan) suggested that RD-1-based commercial IGRAs, using pleural mononuclear cells, appear promising as diagnostic tools for TB-PE [13,14]. In the last several months, two case-control studies from high-burden countries (South Africa) and using QFT-TB-GIT have been published [15,16].…”
Section: Pleural Hbha and Ppd Elispot Responsesmentioning
confidence: 99%
See 1 more Smart Citation
“…Two recent preliminary studies from low-burden countries (Europe and Japan) suggested that RD-1-based commercial IGRAs, using pleural mononuclear cells, appear promising as diagnostic tools for TB-PE [13,14]. In the last several months, two case-control studies from high-burden countries (South Africa) and using QFT-TB-GIT have been published [15,16].…”
Section: Pleural Hbha and Ppd Elispot Responsesmentioning
confidence: 99%
“…We therefore hypothesised that TB antigen-specific responses could distinguish active pleural TB from alternative diagnoses and should have better discriminatory value than unstimulated IFN-c, a nonspecific biomarker of inflammation. A recent case-control study from Europe showed a high diagnostic accuracy with the T-SPOT.1TB assay (Oxford Immunotec, Abingdon, UK) [13] but overall data on the utility of two known IFN-c release assays (IGRAs), T-SPOT.1TB and QuantiFERON1-TB Gold In-tube (QFT-TB-GIT; Cellestis, Carnegie, Australia), including a head-to-head comparison, for the diagnosis of TB-PE are limited [13][14][15][16]. There are several other unresolved questions, including the optimal cell number and pleural fluid volume required, optimal cut-off point and utility in high HIV-prevalence settings [17].…”
mentioning
confidence: 99%
“…Bu nedenle PT hastalarında plevral sıvı İGST ile periferik kan örneği İGST karşılaştırılmıştır. Plevral sıvı T hücre yanıtı birçok çalışmada periferik kan T hücre yanıtına göre daha yüksek bulunmuştur (16)(17)(18)(19). Ariga ve ark.…”
Section: Qft-g Ve Qft-git Testleriunclassified
“…Ariga ve ark. aktif PT hastalarında ESAT-6 ve CFP-10 antijenleri ile aktive ettikleri plevral sıvı IFN-γ cevabı ile periferik kan IFN-γ cevabını ve plevral sıvı ADA seviyelerini karşılaştırmışlardır (16). Antijenlere plevral sıvı IFN-γ cevabı, hem periferik kan IFN-γ cevabı hem de plevral sıvı ADA seviyesine göre anlamlı olarak yüksek bulunmuştur.…”
Section: Qft-g Ve Qft-git Testleriunclassified
“…Despite the fact that IGRA do not discriminate LTBI from active TB, pooled sensitivity of blood assays has recently been estimated to be higher than 80% in detecting active TB disease as a surrogate of TB infection, at least in developed countries (11)(12). Some reports indicate that IGRAs might be helpful in selected cases of pulmonary TB cases (13)(14)(15)(16)(17) and in patients with extra-pulmonary TB, including plTB and TB meningitis, by detecting the release of IFN-y by antigen-specific T cells directly at the infection site (18)(19)(20)(21)(22)(23)(24)(25).…”
mentioning
confidence: 99%